Cognitive Impairment in Heart Failure. (6th June 2012) - Dardiotis, Efthimios; Giamouzis, Gregory; Mastrogiannis, Dimos; Vogiatzi, Christina; Skoularigis, John; Triposkiadis, Filippos; Hadjigeorgiou, Georgios M.
Abstract : Cognitive impairment (CI) is increasingly recognized as a common adverse consequence of heart failure (HF). Although the exact mechanisms remain unclear, microembolism, chronic or intermittent cerebral hypoperfusion, and/or impaired cerebral vessel reactivity that lead to cerebral hypoxia and ischemic brain damage seem to underlie the development of CI in HF. Cognitive decline in HF is characterized by deficits in one or more cognition domains, including attention, memory, executive function, and psychomotor speed. These deficits may affect patients' decision-making capacity and interfere with their ability to comply with treatment requirements, recognize and self-manage disease worsening symptoms. CI may have fluctuations in severity over time, improve with effective HF treatment or progress to dementia. CI is independently associated with disability, mortality, and decreased quality of life of HF patients. It is essential therefore for health professionals in their routine evaluations of HF patients to become familiar with assessment of cognitive performance using standardized screening instruments. Future studies should focus on elucidating the mechanisms that underlie CI in HF and establishing preventive strategies and treatment approaches.